2016
DOI: 10.1016/j.chembiol.2016.05.020
|View full text |Cite
|
Sign up to set email alerts
|

Counter Selection Substrate Library Strategy for Developing Specific Protease Substrates and Probes

Abstract: SUMMARY Legumain (AEP) is a lysosomal cysteine protease that is a lysosomal cysteine protease that was first characterized in leguminous seeds and later discovered in higher eukaryotes. AEP up-regulation is linked to a number of diseases including inflammation, arteriosclerosis and tumorigenesis. Thus legumain is an excellent molecular target for the development of new chemical markers. We deployed a hybrid combinatorial substrate library (HyCoSuL) approach to obtain P1-Asp fluorogenic substrates and biotin-la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
70
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(74 citation statements)
references
References 62 publications
3
70
0
1
Order By: Relevance
“…Advantages of DIPPS were demonstrated also at acidic pH where the profiling revealed that at low pH legumain is turned into an Asn/Asp‐specific protease capable of faster degradation of proteins. These results are in agreement with recent results obtained by combinatorial substrate libraries, which showed that recognition of small substrates by legumain depends solely on the P1 residue (Poreba et al , ). However, the total number of cleavages and the percentage of cleavages after Asp observed in large substrates at acidic pH were much higher as that in small fluorogenic substrates (z‐AAN‐AMC and z‐AAD‐AMC), suggesting differential binding of the substrates.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Advantages of DIPPS were demonstrated also at acidic pH where the profiling revealed that at low pH legumain is turned into an Asn/Asp‐specific protease capable of faster degradation of proteins. These results are in agreement with recent results obtained by combinatorial substrate libraries, which showed that recognition of small substrates by legumain depends solely on the P1 residue (Poreba et al , ). However, the total number of cleavages and the percentage of cleavages after Asp observed in large substrates at acidic pH were much higher as that in small fluorogenic substrates (z‐AAN‐AMC and z‐AAD‐AMC), suggesting differential binding of the substrates.…”
Section: Discussionsupporting
confidence: 93%
“…Human legumain was expressed in the baculovirus expression system (Poreba et al, 2016), whereas human cathepsins K, L, S, and V were expressed in the Pichia pastoris expression system (Invitrogen; Bromme et al, 2004;Mihelic et al, 2008). Active MMP-3 was purchased from Sigma (SRP7783).…”
Section: Expression and Purification Of Recombinant Proteinsmentioning
confidence: 99%
“…This indicated that lansoprazole directly formed S‐S bonds with the SH group of the cysteine in the active site of the proteases. This mechanism was confirmed by using the legumain‐selective activity‐based probe MP‐L01, which binds irreversibly to the active site of legumain . MP‐L01 competed with lansoprazole for binding to legumain and thus confirmed a direct binding of lansoprazole to the active site.…”
Section: Discussionmentioning
confidence: 65%
“…To allow specific activity-based labelling, a fluorogenic coumarin and a diphenyl phosphate warhead are added (Kasperkiewicz et al 2014). This library has previously been used to design probes targeting human proteases (Kasperkiewicz et al 2015;Poreba et al 2016Poreba et al , 2018. Recently, the HyCoSuL methodology was applied to design a probe, WRPK3, which rapidly labels Zika's NS3 protease at low nanomolar concentrations ( Fig.…”
Section: Selective Labelling Of Individual Viral Enzymesmentioning
confidence: 99%